Comparison of Income of Independent Rubber and Palm Oil Farming in Kenaman Village, Sekayam District, Sanggau Regency - penni, Stepenni ste; Kusrini , Novira; Kurniati , Dewi (Jurnal Dinamika Sosial Ekonomi, 2025)
This study compares the income levels of self-managed rubber and oil palm farms in Kenaman Village, focusing on farm management challenges. A quantitative descriptive approach was used, involving 95 farmers. Levene's test indicated homogeneous income variances between the two farm types, while a mean difference test revealed a significant income disparity. The results highlight differences in annual income between rubber and oil palm farming. The results showed that the Levene test produced a result of 0.063 (>0.05), indicating that the rubber and oil palm income data were homogeneous (the T-test results read were the same variance as assumed). Sig. (2-tailed) is 0.000 (<0.05), indicating a significant difference between the annual income of rubber and oil palm farms in Kenaman Village.